INOVASI PELAYANAN TRANSPORTASI PUBLIK BRT (BUS RAPID TRANSIT) TRANS SEMARANG OLEH DINAS PERHUBUNGAN KOTA SEMARANG - Dewi, Chintia Puja; Setianingsih, Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The improvement of the quality of service is necessary to meet all the needs of the community will be mass transport more secure, convenient and affordable service, innovation through the development of public transport BRT Trans Semarang expected level satisfaction can be improved and was able to stimulate the enthusiasm of the community to switch to using public transport services. This research was carried out in order to find out how implementation of the innovation of service of public transport BRT Trans Semarang and restricting factors affecting the implementation of an innovation. Type of this research is descriptive research kind of qualitative data collection process through an in-depth interview studies, informant against the library, documentation and observation. In this study uses the theory of characteristics of an innovation as well as the factors restricting implementation of innovation. The results of this research show that the implementation of innovation services that have been implemented by the public service Agency BRT Trans Semarang is already well underway but not yet at the maximum, that is because expectations and in fact has not been in accordance with the attributes of innovation that should be filled and there are still problems in the implementation, as well as the factors restricting the development of product innovation that is the card E-ticketing and applications playstore BRT that includes the culture of risk aversion, short term budget and planning, inability to face the risk of, there is no reward or incentive, there is technology but is hampered by the cultural and organizational setup, and excess reliance against high performer. The advice given by the researchers is employee training and development, repair the server, created a special team to handle the entire management of innovations, the application of the system of incentives to employees.